Me before you eaudiobook - Moyes, Jojo (Me Before You, 2016)
A recipient of the Romantic Novel of the Year Award from the Romantic Novelists' Association, author Jojo Moyes has had books translated into 11 languages. In Me Before You , Louisa Clark's existence is completely ordinary. But when she takes a job working for wheelchair-bound ex-Master of the Universe Will Traynor, she soon discovers a new purpose in life. Will has lost his desire to live, and Lou tasks herself with changing his mind—and his fate.